High intraspecific ability to adjust both carbon uptake and allocation under light and nutrient reduction in Halimium halimifolium L. - Wegener, Frederik; Beyschlag, Wolfram; Werner, Christiane (Frontiers in Plant Science, 2015)
The allocation of recently assimilated carbon (C) by plants depends on developmental stage and on environmental factors, but the underlying mechanisms are still a matter of debate. In the present study we investigated the regulation of C uptake and allocation and their adjustments during plant growth. We induced different allocation strategies in the Mediterranean shrub Halimium halimifolium L. by a reduction of light (Low L treatment) and nutrient availability (Low N treatment) and analyzed allocation parameters as well as morphological and physiological traits for 15 months. Further, we conducted a 13CO2 pulse-labeling and followed the fate of recently assimilated carbon to eight different tissue classes and respiration for 13 days. The plant responses were remarkably distinct in our study, with mainly morphological/physiological adaptions in case of light reduction and adjustment of C allocation in case of nutrient reduction. The transport of recently assimilated C to the root system was enhanced in amount (c. 200%) and velocity under nutrient limited conditions compared to control plants. Despite the 57% light reduction the total biomass production was not affected in the Low L treatment. The plants probably compensated light reduction by an improvement of their ability to fix C. Thus, our results support